Nová řešení informační podpory pro řízení věřejné správy - Hrabaň, Václav; Šimonová, Stanislava (Univerzita Pardubice, 1999)
The start of new era of information society is expected in close future. Also it would be connected with reformation of public administration mainly in the area of informatics. There are phased in information systems in public administration. Information systems could be supported by additional information technologies mainly for decision support at the control domain. Method of Balanced Scorecard seems to be very convenient for support of top management in organizations. If first-rate implementation of Balanced Scorecard method is done efficiency of work of public administration authorities could be rapidly increased.
Keywords: Informační systémy; Management; veřejná správa